Social movements as agents of innovation: citizen journalism in South Korea - Kern, Thomas; Nam, Sang-hui (GIGA working papers, 2008)
This article aims to further develop the field of innovation studies by exploring the emergence of citizen journalism in South Korea's social movement sector. To achieve this aim, the framework of innovation theory has been extended to innovations in social fields beyond technology and the economy. Our findings show that the emergence of citizen journalism resulted from brokerage activities among journalists, labor and unification activists, and progressive intellectuals. Despite different cultural visions and structural interests, these groups succeeded in building coalitions and constituted a sociocultural milieu which promoted reciprocal learning by allowing actors to realize new ideas and to exchange experiences. The empirical part of the study is based on a social network analysis of social movement groups and alternative media organizations active in South Korea between 1995 and 2002. -- Innovation ; citizen journalism ; social movement ; civil sphere ; social network ; democratization